Self-directed learning readiness of automotive body repair student to face 4.0 learning system - Atmoko Putra Pratama; Herminarto Sofyan; Aan Yudianto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
This study aims to reveal: 1.) Readiness of independent learning of vocational students in the department of automotive body repair to face 4.0 learning systems; and 2.) Supporting and inhibiting factors of students in implementing a 4.0 learning system. This study uses a descriptive-analytical method with a case study approach. The subject consisted of students and teachers of vocational high school majoring in automotive body repair. Data collection techniques in this study were observation, interviews, and questionnaires. The research was conducted at SMK N 2 Depok Sleman, automotive body repair engineering department. 30 respondents filled out the questionnaire to assess the level of self-directed learning readiness of respondents according to SDLR. The readiness level of self-directed learning is divided into three categories: low, medium, and high. The results of this study are (1) Readiness of students majoring in automotive body repair techniques in the face of learning systems 4.0 is included in the medium category, and (2) The supporting and inhibiting factors found in dealing with learning systems 4.0 come from internal and external of the student learning environment.